2020
DOI: 10.21203/rs.3.rs-59561/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Saudi Healthcare Facilities Risk Management and Infection Control Preparedness to Overcome Covid-19 Pandemic

Abstract: Background: The purpose of this study was to evaluate how well prepared Saudi healthcare facilities to overcome COVID-19 pandemic. Methods: A cross-sectional study was conducted using online-administered English questionnaire that distributed throughout Saudi commission for health specialities at Saudi hospital during the period of April-June 2020. The questionnaire represent a minimum level of knowledge and practices for all components of risk management and infection control and prevention program which shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The individuals were observed to have deteriorated in terms of health and mental peace during the beginning stages of the COVID-19 pandemic. A study by Alhasan et al has also reported a negative impact of COVID-19 on the educational systems and healthcare sectors, as well as the individual well-being of the people and clinical practitioners in Saudi Arabia 19 . Another cross-sectional study conducted by Almufarrijiet al 20 has reported the impact of COVID-19 on neurosurgery clinical practitioners in Saudi Arabia.…”
Section: Saudi Arabian Population and Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The individuals were observed to have deteriorated in terms of health and mental peace during the beginning stages of the COVID-19 pandemic. A study by Alhasan et al has also reported a negative impact of COVID-19 on the educational systems and healthcare sectors, as well as the individual well-being of the people and clinical practitioners in Saudi Arabia 19 . Another cross-sectional study conducted by Almufarrijiet al 20 has reported the impact of COVID-19 on neurosurgery clinical practitioners in Saudi Arabia.…”
Section: Saudi Arabian Population and Covid-19 Pandemicmentioning
confidence: 99%
“…The significant coronavirus infections that have caused a huge impact on the human world include three pandemics such as the severe acute respiratory syndrome (SARS); the Middle East Respiratory Syndrome (MERS); and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the years 2002 to 2003, 2012, and 2019, respectively. On comparing these three significant infections, a highly negative impact has been caused by coronavirus disease 2019 (COVID- 19), which was caused due to SARS-CoV-2 [2][3][4] On March 11 th , 2020, COVID-19 has been declared as a pandemic by the World Health Organization (WHO). According to the Centre for Disease and Control Prevention, the infective agent of COVID-19 is the seventh member of the coronavirus family discovered so far.…”
Section: Introductionmentioning
confidence: 99%
“…2 Saudi Arabian hospitals and other health facilities play a key role in the national and local responses to the COVID-19 pandemic. 3 The current research proposal focuses on evaluating how these hospitals and facilities work on a global scale. The COVID-19 pandemic experience can recommend procedures and guidelines that can be applied to the management of other emergencies.…”
mentioning
confidence: 99%